(untitled) (Research, Society and Development, 2021)
The use of dental composites has grown in recent years due to the increase in aesthetic demand and the emergence of new technologies. The degree of conversion is directly related to its degree of hardness. This study evaluated the influence of depth of cure, time and storage medium on the surface hardness of dental composites. Three composite resins were used: Filtek Z250 XT (3M/ESPE), Filtek Bulk Fill (3M/ESPE) and Tetric N-Ceram Bulk Fill (Ivoclar Vivadent). Twenty specimens were made for each material, 10 for each immersion medium (water and 75% ethanol/water solution) and 10 for each depth of cure (0 mm, 2.0 mm and 4.0 mm) for evaluation the hardness of the top, middle and base of each specimen. For the initial hardness test, three indentations were performed on each surface with a load of 50 kgf, for 15 seconds in a microdurometer. Then, the specimens were stored individually in storage media at 37°C for periods of 24 hours, 90 days and 180 days. All dental composites evaluated showed a significant reduction in hardness with increasing depth of cure. The composites showed a reduction in the average surface hardness values over time, being more pronounced in storage with an alcohol solution. The microhardness of all composite resins reduced with increasing depth of cure. The storage medium influenced the surface microhardness, being more pronounced for the storage medium, a 75% ethanol solution.